‘Love at first sight’: The effect of personality and colouration patterns in the reproductive success of zebrafish (Danio rerio) - Vargas, Reynaldo (PLoS One, 2018)
Individual differences in animal personality and external appearance such as colouration patterns have both been extensively studied separately. A significant body of research has explored many of pertinent ecological and biological aspects that can be affected by them and their impact upon fitness. Currently little is known about how both factors interact and their effect on reproductive success. In this study, we evaluated two major parameters contributing to the fitness of the species: reproduction and offspring survival. We selected two different phenotypes of the zebrafish (Danio rerio) selected by their colouration patterns: phenotype 1) named Wild type, UAB line (WT-UAB) with a homogeneous colouration pattern (clear and defined lateral stripes) and phenotype 2) Wild type indefinite (WT-I) had a heterogeneous colouration pattern and different degrees of lateral stripe definition. All animals were also screened for personality. We then compared their reproductive success (spawning rate) and offspring survival at different stages, from egg to larvae, and for 2 successive generations (parental generation was G0; First and second generations were G1 and G2 respectively). Our results show that personality traits were the main source of variability between the fitness components measured: both personalities had similar total numbers of eggs spawned but proactive animals, for both colour phenotypes, had higher reproductive success. This was reflected in a higher percentage of spawning viability at 1day post fertilization (dpf), higher total survival and growth rates at larval stages. Proactive phenotypes from WT-UAB population had a higher overall fitness in comparison to the other phenotypes studied. Our findings imply that fitness of this species when kept under similar husbandry conditions is significantly influenced by parental personality and not by their external appearance. Under these conditions the reproductive success is enhanced. The implications of this study are important for zebrafish breeding and husbandry in captivity and are relevant toward understanding the underlying drivers of trait selection in natural environments.